Unusual Cause of Mitral Regurgitation - Kader Muneer; Sajeer Kalathingathodika; Madurai Shanmugasundaram Shivendrran; Vipin Das (Journal of the Indian Academy of Echocardiography & Cardiovascular Imaging)
A 1-month-old neonate was referred due to poor feeding and failure to thrive. On examination, the child had a short systolic murmur at the apex. The echocardiogram revealed moderate mitral regurgitation, hyperechoic papillary muscle, and retrograde flow from the left coronary artery (LCA) into the pulmonary artery (PA), indicating an anomalous LCA from the PA (ALCAPA). The LCA arose from the nonfacing sinus of the PA, a rare and complex presentation, which makes surgery challenging. ALCAPA is a life-threatening condition, and early diagnosis and surgery are crucial. The child underwent successful surgery elsewhere and is stable on follow-up.